Vulnerability of Tribal Communities to Climate Variability in Lahaul and Spiti, Himachal Pradesh, India - Pankaj Kumar; Ashwanı; Satyam Mıshra; Swati Thakur; Dilip Kumar; V.a.v Raman (Coğrafya Dergisi)
India is home to many physiographic divisions, climatic regions, diverse cultures, and ethnicities. The greater Himalayan and trans-Himalayan regions are home to many tribal communities. However, climatic variability brings new challenges to the tribal households in mountainous regions, particularly in India’s greater Himalayan and trans-Himalayan regions. This study aims to create a Tribal Household Livelihood Vulnerability Index (THLVI) that takes into account factors such as exposure, sensitivity, and adaptive capacity. The research focuses on three subdivisions in the Lahaul and Spiti district, namely: Lahaul, Udaipur and Spiti, which are part of the western Himalayas cold deserts. The data for the THLVI was collected from 300 randomly selected households in 62 villages through a survey of indigenous people. The results of the study reveal that the vulnerability of tribal households varies across different socio economic and ecological conditions due to differences in adaptability, sensitivity, and exposure to climate change. In the Lahaul and Udaipur subdivisions, the vulnerabilities of social networks, water, and health were found to be 0.390, 0.262, 0.545, and 0.525, 0.514, 0.512, respectively. The THLVI based on IPCC values ranges from -1 (least vulnerable) to +1 (most vulnerable). For further research, the THLVI index can be used as a tool to assess the livelihood vulnerability of tribal communities living in Himalayan regions, furthermore the sustainable livelihood policies can be formulated in order to strengthen the livelihood security